Bamboo Diversity in Indrokilo Botanical Garden, Central Java - Baiq Farhatul Wahidah; I Putu Gede P. Damayanto; Sri Mulyani (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2021)
The efforts of Bamboo conservation have been conducted by botanical gardens in Indonesia, including the Indrokilo Botanical Garden, Central Java. Scientific information regarding the bamboo collection of the Indrokilo Botanical Garden, however, is not yet available. This study aimed to determine the diversity of the species, as well as, to provide a synopsis and the similarity analysis of the bamboo species in the Indrokilo Botanical Garden. Exploration and collection of bamboo specimens have been carried out by the Indrokilo Botanical Garden. Processing and identification of the specimens were carried out at Herbarium Bogoriense. A total of 27 morphological characters were used for similarity analysis using the UPGMA method with Nei & Li similarity coefficients. The data were analyzed descriptively. There are seven species of bamboo in the Indrokilo Botanical Garden: Bambusa glaucophylla, B. lako, B. multiplex, B. vulgaris, Dendrocalamus sp., Guadua cf. angustifolia, and Schizostachyum sp. A synopsis of the bamboo species and their identification keys to the species were provided. Based on the similarity analysis, bamboo in the Indrokilo Botanical Garden consists of five groups at a similarity index of 70%. The diversity of bamboo species in the Indrokilo Botanical Garden is relatively low compared to some botanical gardens in Indonesia.